Memories of the counterculture through the lens of Irwin Klein. Issue 1 (2nd January 2017) - Klein, Benjamin
Abstract: The author of this essay reflects upon his experience with the counterculture in northern New Mexico and his relationship to his uncle, the late photographer Irwin Klein (1933–1974).